GEOLOGI DAN PENGARUH INTRUSI TERHADAP KUALITAS BATUBARA SEAM A1 DAN A2 FORMASI MUARA ENIM DAERAH TAMBANG AIR LAYA, KECAMATAN LAWANG KIDUL,KABUPATEN MUARA ENIM, PROVINSI SUMATERA SELATAN - Adhimas Permana Putra (Jurnal Ilmiah Geologi PANGEA, 2016)
ABSTRACK - Intrusion is one of reasons that caused difference of coal rank. Changes in coal rank due to bypressure and temperature which occurs in particular time and pressure by intrusion. In order to determine coalrank, which can be done by ProximateAnalyzing( Chemistry Test, ASTM). Which determining percentage ofmoisture, volatile matter, fixed carbon, and ash with a certain method at general coal laboratory. Effect ofintrusion in coal rankis not too extensive, it only affect the area that have direct contact to the intrusion. Thecloser the coal to the intrusion, the more possibility of better rank than the coal that further to the intrusion.Key words : intrution, coal rank.